A reflexive critique of a critical hermeneutics analysis of Wu Zetian. Issue 3 (10th September 2018) - Yu, Tianyuan; Mills, Albert J.; Peng, Niya
Abstract : Purpose: Revisiting the critical hermeneutics analysis of Wu Zetian's case in Peng et al. 's (2015) paper, the purpose of this paper is to explore the complexity and paradox of Wu Zetian as a historical figure, and to demonstrate the potential of critical hermeneutics as an innovative methodology to study gender, diversity and history. Moreover, the authors attempt to examine some of the potential challenges and limitations of this methodology and to provide an in-depth account of the socio-politics involved in the research process. Design/methodology/approach: This is a reflexive critique based on a framework of four central concepts of critical hermeneutics (Prasad, 2005): questions of author intentionality, layers of texts, hermeneutic circle and relating to texts. Findings: Critical hermeneutics has great potential as well as considerable challenges and limitations in the research areas of gender, diversity and history. Originality/value: This paper offers a lucid exposition of what critical hermeneutics is about, how it might be applied to a particular case and potential challenges and limitations of this methodology. The study is intensely reflexive and context oriented, illustrating how a deepened understanding of critical hermeneutics leads to a more informed discussion of the possibilities and limitations of the methodology, and how researchers, editors and reviewers can be influenced by the context in which the study is conducted.